Influence of 36 years of integrated nutrient management on soil carbon sequestration, environmental footprint and agronomic productivity of wheat under rice-wheat cropping system - Ranjan, Shivani; Kumar, Sanjay; Dutta, Swaraj Kumar; Padhan, Smruti Ranjan; Dayal, Parmeswar; Sow, Sumit; Roy, Dhirendra Kumar; Nath, Dibyajyoti; Baral, Kirttiranjan; Bharati, Vikram (Frontiers in Environmental Science, 2023)
A long-term field experiment was conducted to study the effects of different combinations of integrated nutrient management (INM) on carbon sequestration and wheat yield in a rice-wheat cropping system. The experiment consisted of 11 treatments that were replicated three times. The organic manures used in the study included farmyard manure (FYM), wheat straw (WS), and green manure (GM) with Sesbania aculeata. The results of the experiment revealed that the application of 50% of the recommended dose of fertilizers (RDF) along with 50% nitrogen (N) through FYM during rice cultivation, and RDF during wheat cultivation, led to a significant increase in soil organic carbon (SOC). Specifically, the SOC content was enhanced by 46.4% (18.29 Mg ha-1) compared to RDF in rice and wheat, resulting in a C sequestration rate of 0.22 Mg ha-1 year-1. These increases were higher in treatments that combined organic and inorganic inputs. Additionally, the application of 50% RDF and substituting 50% of the nitrogen with FYM during wheat cultivation resulted in a 24.7% increase in grain yield compared to RDF in rice and wheat. The INM treatments, showed significantly (p ≤ 0.05) higher agronomic efficiency (AE) of nitrogen (N), phosphorus (P) and potassium (K), partial factor productivity (PFP) of N, P and K, and carbon pool index (CPI) compared to the application of inorganic fertilizers at the recommended dose. Moreover, the INM treatments also exhibited lower greenhouse gas (GHG) emission intensity. Application of neither chemical fertilizers nor organic manure (T1) resulted in maximum GHG emission intensity (328.1 kg CO2 eq Mg−1 yield). Based on these findings, it can be concluded that the combined use of inorganic fertilizers and organic manures significantly increased crop yield and soil organic carbon sequestration while reducing GHG emissions in a rice-wheat cropping system in the eastern Indo-Gangetic Plains (EIGP) of India.